Supervisi Kepala Sekolah Untuk Meningkatkan Penilaian Kinerja Pendidik di SDN 7 Padang Sibusuk - Idola, Doni Masria; Asmendri, Asmendri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Abstract : Teachers are one of the most important factors in an educational organization in order to achieve the goals of an educational organization. Such satisfactory performance will not just happen in an organization. Evaluation of a teacher's performance needs to be done in order to see the progress of a teacher's performance, this evaluation is not necessarily carried out only within a certain period of time, but must be carried out continuously every month. In this study, the purpose of this study was to determine the extent of performance appraisal through educational supervision carried out by school principals to improve teacher performance. This study uses descriptive qualitative research, the subject is the principal, the teacher assembly, and other teacher activities. Data collection techniques used are interviews, observation, and documentation. The results of the study show that the assessment carried out by the principal on the teacher's performance starts from the planning carried out by the principal by determining the teacher supervision schedule, organizing the implementation carried out by the principal during the teaching and learning process. The implementation of teacher performance assessment activities is carried out every month through classroom supervision activities, supervision is carried out by the principal directly when the activity takes place, the inhibiting factor found is that there are still many teachers who are still lacking in operating IT in learning while the supporting factor is that schools have adequate facilities and infrastructure. adequate.